TINJAUAN YURIDIS TERHADAP PENGGUNA NARKOTIKA YANG MELAPORKAN DIRI KE BADAN NARKOTIKA NASIONAL DAN MENDAPATKAN REHABILITASI - Agum Andi Matalata (Universitas 17 Agustus 1945 Samarinda, 2016)
ABSTRACTAt first drug used only as a tool for religious rituals and in addition it is also used for treatment, the type of drug used in the beginning was the opiate or commonly known as opium or opium. However, with the development of the times, the drug used for negative things, in the world of medicine narcotic widely used, especially in the process of patient's anesthesia before surgery. Along with the times as well, someone who at first lay against narcotics turned into an addict is difficult regardless of dependence.Addicts are